Temperature variability in the tropical mesosphere during the northern hemisphere winter - Shepherd, M.G.; Wu, D.L.; Fedulina, I.N.; Gurubaran, S. (My University, 2008)
Temperature observations at 20–90 km height and 5°N–15°N during the period of December 1992–March 1993 from the WINDII and MLS experiments on the UARS satellite are analysed together with MF radar winds and UKMO assimilated fields of temperature and zonal and meridional winds. The correlation between the different datasets at the tropics and zonal mean wind data at mid latitudes is examined for period February–March 1993, when series of stratospheric warming events were observed at middle and high latitudes. Wavelet analysis is applied to investigate coupling between stationary and travelling planetary waves in the stratosphere and the upper mesosphere. Planetary waves m = 1 with periods of 4–7 days, 8–12 days and 13–18 days are found to dominate the period. Westward 7- and 16–18 day waves at the tropics appear enhanced by stationary planetary waves during sudden stratospheric warming events.
Keywords: Temperature; Zonal winds; Tropical mesosphere; Stratospheric warming; Planetary waves